EDUKASI TEKNIK PENYELAMAN YANG SEHAT PADA PENYELAM TRADISIONAL DI DESA BAJO INDAH KEC. SOROPIA - Muhaimin Saranani; Nurfantri; Rundu (Health Care : Journal of Community Service, 2024)
Background : Traditional diving is a major source of livelihood for some Indonesian coastal communities, especially for fishing and other marine products. However, diving practices that do not comply with safety standards often pose serious health risks, particularly vascular and cardiac disorders (Wabula, 2019). Knowing the description of decompression sickness, how to prevent / minimize the risk of decompression by diving properly / healthy and using alternative fishing methods in Bajo Indah Village, Soropia Kec. Konawe Regency. Methods. Providing education in the form of counseling and demonstration, the target of this activity is traditional divers in Bajo Indah village, Soropia sub-district, Konawe, totaling 30 people. Indicators of the success of the intervention through measuring the level of knowledge, which was carried out before and after conducting education, Result:. There was a change in the number of respondents' knowledge levels before and after providing education, it appeared that the percentage of respondents with poor knowledge (19 respondents or 63%) and 8 respondents or 26% decreased with the number of respondents with low knowledge being 3 respondents (10%) and with sufficient knowledge increasing to 12 respondents (40%).